Analisis Rasio Likuiditas dan Rasio Profitabilitas dalam Mengukur Kinerja Keuangan PT Telekomunikasi Indonesia Tbk Periode 2024-2025 - Afifah Nada Thahirah; Aliya Salsabilla; Fiqri Erlansyah; Muhammad Fadhilah Rasya Sanduan; Angga Sanita Putra (Business and Investment Review, 2026)
Abstract This study evaluates the financial performance of PT Telekomunikasi Indonesia Tbk through an analysis of its financial statements for the 2024–2025 period. Using a descriptive quantitative approach, the research employs secondary data obtained from the Indonesia Stock Exchange (IDX) and the company’s published financial reports. The analysis is conducted using liquidity and profitability ratios, including the Current Ratio, Quick Ratio, Cash Ratio, Return on Assets (ROA), and Return on Equity (ROE). The findings indicate that the company experienced a slight improvement in liquidity, reflecting a better ability to meet its short-term obligations. This improvement was supported by prudent debt management, which reduced the company’s dependence on external financing. However, profitability performance showed a declining trend, as evidenced by lower ROA and ROE values during the study period. Furthermore, although the company maintained a relatively stable financial position, its overall financial performance remained below the industry benchmarks used in this study. These results suggest that PT Telekomunikasi Indonesia Tbk needs to improve operational efficiency, optimize the utilization of assets and equity, and strengthen its profit-generation capabilities in order to enhance its competitiveness and achieve better financial performance in the future. Keywords: Financial Statement Analysis, Liquidity Ratios, Profitability Ratios, Financial Performance. Abstrak: Studi ini mengevaluasi kinerja finansial PT. Telekomunikasi Indonesia Tbk. melalui analisis laporan keuangan untuk periode 2024–2025. Dengan menerapkan metode kuantitatif deskriptif, penelitian ini mengolah data sekunder yang bersumber dari Bursa Efek Indonesia (BEI) menggunakan indikator rasio likuiditas dan profitabilitas. Temuan penelitian mengungkapkan bahwa perusahaan memiliki tingkat likuiditas yang sehat guna menyelesaikan kewajiban jangka pendeknya, didukung oleh manajemen utang yang bijak sehingga mengurangi ketergantungan pada modal eksternal. Meskipun profitabilitas yang diukur melalui Return on Assets (ROA) dan Return on Equity (ROE) bergerak ke arah positif, capaian performa keuangan menyeluruh emiten ini tercatat masih belum mampu melampaui rata-rata standar industri sejenis. Kata Kunci: Analisis Laporan Keuangan, Rasio Likuiditas, Rasio Profitabilitas